An innovative approach: Agile methodologies for the design of power circuit breakers - Monteiro, Paulo Roberto Duailibe; Borges, Thiago Trezza; Schiochet, André Fernando (Seven Editora, 2024)
During the increasing complexity of electrical systems, the need for more effective and accessible methods becomes evident, seeking to balance technical precision, operational practicality and safety. This article proposes an innovative and simplified method for the sizing of power circuit breakers, aiming to optimize the efficiency of the selection process of these crucial equipment for the electrical infrastructure. The sizing methodology aimed at specifying the main characteristics of power circuit breakers offers a systematic and comprehensive approach, integrating critical considerations ensuring the correct functioning of these equipment in various electrical contexts. The process consists of several steps, covering everything from the initial analysis to the final selection of the appropriate circuit breaker. The modified power method is applied to the definition of the short-circuit characteristics and is introduced in the sizing criteria based on the operation of the electrical system for the analysis in normal operation of the system. A test system of a pumping station consisting of a 69 kV substation is studied. The proposed methodology met its objectives, presenting precision and effectiveness, and can be a very useful tool for project engineers in electricity. DOI:https://doi.org/10.56238/sevened2024.004-005